Perceived mental illness stigma and self stigma among persons treated for psychotic disorders - A. Jambrosic Sakoman; T. Jendričko; D. Bošnjak Kuharić; A. Tomić (European Psychiatry, 2024)
Introduction Stigma related to mental health has serious impact on persons suffering from psychiatric disorders and on their families. Self-stigma occurs when people with mental health problems internalize public attitudes, negative beliefs and stereotypes associated with psychiatric disorders. Stigma and self-stigma can affect every aspect of life and result in discrimination, social exclusion, feelings of low self-esteem, shame, guilt, and can postpone seeking help.